2009
DOI: 10.1063/1.3274815
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical characteristics of the bound states of M-X complexes (M=Cu, Ag, and Au, and X=He, Ne, and Ar)

Abstract: The potential energy curves (PECs) of the bound states of M-X (M=Cu, Ag, and Au and X=He, Ne, and Ar) complexes have been calculated using the coupled cluster singles and doubles method with perturbative treatment of triple excitations. Large basis sets and bond functions, as well as the basis set superposition errors, are employed to obtain accurate PECs. The analytical potential energy functions (APEFs) are fitted using the PECs. The vibrational energy levels and the spectroscopic parameters for the complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…For the lowest energy of the Ag n Si (n = 1 -9) clusters, the HOMO-LUMO gaps for the most stable Ag n Si and Ag n+1 clusters against the cluster size are plotted in Figure 3. The trend of the Ag n Si and Ag n+1 clusters show a contrary odd-even oscillation similar to ∆E(n) and ∆ 2 E(n), which implies that Ag 2,4,6,8 Si and Ag 3,5,7,9 clusters have an enhanced stability compared with their neighbour clusters. Interestingly, the significant peak is also localized at n = 4 and the Ag 4 Si isomer has the largest HOMO-LUMO gap of 2.54 eV.…”
Section: Homo-lumo Gaps and Charge Transfermentioning
confidence: 74%
See 3 more Smart Citations
“…For the lowest energy of the Ag n Si (n = 1 -9) clusters, the HOMO-LUMO gaps for the most stable Ag n Si and Ag n+1 clusters against the cluster size are plotted in Figure 3. The trend of the Ag n Si and Ag n+1 clusters show a contrary odd-even oscillation similar to ∆E(n) and ∆ 2 E(n), which implies that Ag 2,4,6,8 Si and Ag 3,5,7,9 clusters have an enhanced stability compared with their neighbour clusters. Interestingly, the significant peak is also localized at n = 4 and the Ag 4 Si isomer has the largest HOMO-LUMO gap of 2.54 eV.…”
Section: Homo-lumo Gaps and Charge Transfermentioning
confidence: 74%
“…(ii) By analyzing the relative stabilities of the Ag n Si (n = 1 -9) clusters, we found that the Ag 4 Si isomer shows the strongest stability due to its local peak in all the curves of E b (n), ∆E(n), ∆ 2 E(n), E dis (n), and HOMO-LUMO gaps. The HOMO-LUMO gaps show a contrary odd-even oscillation, which implies that Ag 2,4,6,8 Si and Ag 3,5,7,9 clusters have enhanced stability compared with their neighbours. (iii) The charges in Ag n Si (n = 1 -9) clusters transfer from the Ag n frames to the silicon atom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once again, the dopant-helium interaction enters the functional as V external , but now has the form suggested by Tong et al 22 …”
Section: Droplets With Transition Metal Dopantsmentioning
confidence: 99%